Eat sleep sit: my year at Japan's most rigorous Zen temple - Nonomura, Kaoru (Kodansha International, 2008)
Pilgrim -- Jizo cloister -- Dragon gate -- Main gate -- Temporary quarters -- Toilet -- Facing the wall -- Buddha bowl -- Evening service -- Evening meal -- Night sitting -- Etiquette is zen -- Morning service -- Morning meal -- Cleaning the corridors -- Dignified dress -- Washing the face -- Verses -- Noon -- Stick -- Alone in the freezing dark -- Entering the hall -- Monks? hall -- New residence -- Wake-up bell -- Bell tower -- Self-reflection -- Food server -- Monks? food -- Shaving the head -- Daikan -- Hunger -- The principle of the flow of time -- Escape -- Registration ceremony -- First bath -- Beginning intensive training -- Manual labor -- Penance -- Main lecture -- Transfer -- The source of the warmth of light -- New job -- Sales -- Distribution of goods -- Guest pavilion -- Inspection -- Washrags -- Ending intensive training -- The color of the peak, the echo in the valley -- Attendant to the administrator -- Conference room -- In attendance -- Morning session -- Incense bearer -- Preparations for winter -- Intensive sitting -- Year-end cleaning -- New year?s day -- New arrivals -- Just sit -- Departure survey -- Leaving